Peningkatan Prestasi Belajar Siswa Melalui Model STAD (Student Team Achievment Divisions) Pada Kelas VIII Di Smp Negeri 3 Peureulak - Afwiyah (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
This research aims to improve the learning achievement of class VIII students at SMP Negeri 3 Peureulak through the application of the STAD (Student Team Achievement Divisions) model. This cooperative learning model emphasizes cooperation in groups to achieve common goals. This research involves the process of group formation, explanation of material, division of tasks, monitoring, group evaluation, appreciation, reflection, and continuous learning. The research method used was classroom action research (PTK) which involved one class VIII as the research subject. The research results show a significant increase in student learning achievement after implementing the STAD model. Forming groups with a diversity of student abilities, dividing tasks that require cooperation, and group evaluations provide positive contributions to student academic achievement. Increasing student learning achievement is also supported by parental involvement and consistent implementation of the STAD model in the curriculum. In the learning process, students not only develop a deep understanding of concepts but also social skills and teamwork. It is hoped that the results of this research can contribute to the development of more effective learning strategies in the educational environment.